1981
DOI: 10.1111/j.1550-7408.1981.tb02844.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Development of Eimerian Coccidia in Sandhill and Whopping Cranes1

Abstract: In contrast with isosporoid species of coccidia that have established extraintestinal phases of development, the eimeriids, except for a few species, generally have been considered inhabitants of the intestinal tract. Eimeria infection in sandhill cranes (Grus canadensis) and whooping cranes (G. americana) may result in disseminated visceral coccidiosis. Nodules were observed in the oral cavity of 33% (n = 95) of the G. canadensis at the Patuxent Wildlife Research Center (PWRC) in Laurel, MD. Necropsy of six o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 0 publications
0
38
0
Order By: Relevance
“…The route of migration in other hepatic species of coccidia is unclear; however, both lymphatic and haematogenous spread have been implicated (Smetana, 1933;Horton, 1967;Pakandl, 2009). Asexual and sexual stages of E. reichenowi and E. gruis in cranes occur primarily in macrophages, and it is suggested that these species use this route to penetrate into the blood and/or lymphatic system (Novilla et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…The route of migration in other hepatic species of coccidia is unclear; however, both lymphatic and haematogenous spread have been implicated (Smetana, 1933;Horton, 1967;Pakandl, 2009). Asexual and sexual stages of E. reichenowi and E. gruis in cranes occur primarily in macrophages, and it is suggested that these species use this route to penetrate into the blood and/or lymphatic system (Novilla et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Eimeria stiedae completes its life-cycle in the bile ducts of rabbits (Mykytowycz, 1962). Schizogenous and gametogenous stages of the endogenous life-cycle of intestinal Eimeria spp have been found in the testes, ovary, swim-bladder, liver, kidney and spleen offish (Overstreet, 1981), in the liver, spleen, heart and lung of cranes, Grus canadensis and G. americana (Novilla et al, 1981), and in the livers of pigs (Desser, 1978). Sporozoites of E. maxima were found in the liver of guinea fowl, Numida meleagris, and chickens inoculated with oocysts via the crop (Long and Millard, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Although coccidia of the genus Eimeria are protozoan parasites that usually invade the intestinal tract, a few eimerians of mammals and birds develop in extraintestinal sites (Courtney et al, 1975;Desser, 1978;Forrester et al, 1978;Lima, 1979;Novilla et al, 1981). In birds, Eimeria truncata normally infects the kidneys of geese and ducks (Wobeser and Stockdale, 1983;Oksanen, 1994), and Eimeria reichenowi and Eimeria gruis of cranes have been found in other visceral organs of wild sandhill cranes (Grus canadensis) and whooping cranes (Grus americana) (Carpenter et al, 1979(Carpenter et al, , 1980.…”
mentioning
confidence: 99%
“…In birds, Eimeria truncata normally infects the kidneys of geese and ducks (Wobeser and Stockdale, 1983;Oksanen, 1994), and Eimeria reichenowi and Eimeria gruis of cranes have been found in other visceral organs of wild sandhill cranes (Grus canadensis) and whooping cranes (Grus americana) (Carpenter et al, 1979(Carpenter et al, , 1980. In cranes infected with eimeriid coccidia, the resulting disease, disseminated visceral coccidiosis (DVC), can be grossly evident as small, white, raised granulomatous nodules on the surface of organs that contain developmental stages of the eimerian coccidia (Novilla et al, 1981;Carpenter et al, 1984).…”
mentioning
confidence: 99%